2021
DOI: 10.1002/advs.202002548
|View full text |Cite
|
Sign up to set email alerts
|

Harnessing X‐Ray Energy‐Dependent Attenuation of Bismuth‐Based Nanoprobes for Accurate Diagnosis of Liver Fibrosis

Abstract: Timely detection of liver fibrosis by X‐ray computed tomography (CT) can prevent its progression to fatal liver diseases. However, it remains quite challenging because conventional CT can only identify the difference in density instead of X‐ray attenuation characteristics. Spectral CT can generate monochromatic imaging to specify X‐ray attenuation characteristics of the scanned matter. Herein, an X‐ray energy‐dependent attenuation strategy originated from bismuth (Bi)‐based nanoprobes (BiF3@PDA@HA) is proposed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 47 publications
0
13
0
Order By: Relevance
“…The image also shows the energy-dependent attenuation of the targeted region after BiF 3 @PDA@HA NPs injection in the in vivo model, and changes in the spectral house units (HU) of the liver and tissue at different energy attenuations. Furthermore, because of the energy-dependent attenuation of Bi, the diseased area could be suitable for selecting different monochromatic energies via spectral CT. 87…”
Section: Bismuth (83) Nanoparticlesmentioning
confidence: 99%
“…The image also shows the energy-dependent attenuation of the targeted region after BiF 3 @PDA@HA NPs injection in the in vivo model, and changes in the spectral house units (HU) of the liver and tissue at different energy attenuations. Furthermore, because of the energy-dependent attenuation of Bi, the diseased area could be suitable for selecting different monochromatic energies via spectral CT. 87…”
Section: Bismuth (83) Nanoparticlesmentioning
confidence: 99%
“…[246][247][248] Therefore, it is very important to distinguish between the various stages of liver fibrosis as the degree of fibrosis is closely linked with therapeutic decision-making. [249][250][251][252][253] Yang et al developed a protein-based MRI contrast agent (namely ProCA32.collagen1) for quantitatively mapping levels of collagen I in chronic liver A-C) Reproduced with permission. [240] Copyright 2021, American Chemical Society.…”
Section: Biomarker-responsive Nanotheranostics For Chronic Liver Dise...mentioning
confidence: 99%
“…Hyaluronic acid-coated Bi 2 O 3 NPs showed multiple activities by exhibiting efficient attenuation of X-rays along with providing radiosensitization causing cell apoptosis. In this way, the developed system could be a potential candidate for CT imaging guided radiotherapy of tumors due to the low cost of bismuth element as compared to gold and higher radiosensitization. , Similarly, other bismuth-based nanoparticles (such as Bi 2 S 3 NPs and Bi 2 Se 3 nanoplates) and tungsten trioxide NPs are also able to attenuate X-rays with high efficiency. However, few studies have reported the application of theranostics by combining polysaccharides with bismuth and tungsten-based nanoparticles. , due to the lack of functional groups for post-modification and difficulty in controlling their shape and size.…”
Section: Polysaccharide-based Theranosticsmentioning
confidence: 99%